The impact of whitegrub (Coleoptera: Scarabaeidae) damage on growth of Eucalyptus grandis and Acacia mearnsii plantation trees in South Africa. Issue 2 (3rd April 2022) - Echeverri-Molina, Derian; Govender, P.
ABSTRACT: Eucalyptus grandis and Acacia mearnsii are among the South African forest industry's most planted commercial species. Whitegrubs are high-status pests affecting plantation forestry; they are root-feeding insects and cause poor seedling growth and elevated mortality. The aim of this study was to elucidate the impact of whitegrub damage on the growth of E. grandis and A. mearnsii trees during the first year of the establishment stage in sites previously planted with A. mearnsii in the KwaZulu-Natal Midlands of South Africa. The hypothesis was that the prophylactic application of insecticides against whitegrubs would increase tree height at six or 12 months after planting. Seven insecticides were assessed in 12 treatments over three trials in Bloemendal, KwaZulu-Natal. Statistical analyses were performed using PRIMER and SAS. Whitegrubs were the predominant mortality factor (17.1%), followed by pathogens (3.3%) and 12 other factors that cumulatively caused the remaining (7.0%) mortality. Pegylis sommeri, Schizonycha affinis and two unknown Maladera species were the most important, typical and prevalent whitegrub species, but their ranking differed between A. mearnsii and E. grandis, suggesting a host preference. The prophylactic application of insecticides against whitegrubs significantly increased tree height for E. grandis. Acacia mearnsii tree height, however, did not consistently show a significant effect with insecticide control, presumably because of additional mortality by pathogens. The crop-rotation scenario may have potentially benefited E. grandis over A. mearnsii and warrants further investigation. Whitegrubs can kill seedlings and reduce tree height when left uncontrolled.